Determination of Equilibrium Moisture Content in Trade Distribution - Marpaung, David Septian Sumanto; Indryani, Anggia; Sinaga, Ayu Oshin Yap (Journal of Agriculture and Applied Biology, 2020)
Maize is one of essential crop in Indonesia. Maize trade distribution showed economic condition in society. If the distribution trade was poor, the quality and quantity of product will be low, consequences to uncontrolled condition in society. Every actor in distribution trade play important role. Farmer for instance, if the farmer produces low quality of maize grain, will resulted unacceptable product in factory. The acceptance of maize in feed factory is determined by several factor, such as moisture content, microorganism contamination, and presence of pest. To know the best recommendation treatment to prevent rejected product in feed factory, it is important to de-termine the moisture content in trade distribution, because the higher mois-ture content would increases the possibility of microorganism contamina-tion. Besides, the best condition storage is also critical for keeping the quali-ty of maize grain. Therefore, determination of equilibrium moisture content (EMC) will help the policies maker to consider environment condition for their storage. In this study, the maize EMC was determined using Hender-son’s equation. The results showed that the highest EMC was found in the maize after threshing (23.49±0.58%). The postharvest treatment, such as drying and sortation is very important apply in such point